Factors affecting loan performance: A case study of CRDB Bank Plc in Mwanza region - Gilbert, Happy (Mzumbe University, 2024)
A research report submitted for the partial fulfillment of the requirements for the award of the Masters of Science in Accounting and Finance at Mzumbe University